Visual culture: Threshold of knowledge - Julio César Goyes Narváez (Corporación Universitaria Minuto de Dios, 2011)
This paper presents an analysis of the image as the basis of visual culture and its most important characteristics in the social context and the field of knowledge that make up his studies and practices. Culture as battlefield and structuring of production processes, distribution and reception and its relationship with the media or broadcast, the concept of culture that manages education, art, ways of social behavior as a handbook, and especially as refinement, as if it only depended on the economics and hide the confrontation with diverse and succulent meals of social and cultural reality. The visual and the order of the gaze. The gaze that submits the eye to an invasion of culturally agreed meanings or in process of transformation, from production, circulation, reception and media consumption of the image and the implications in the educational process.